Peri-implant Bone Healing: Its Basic Osteogenesis and Biomarkers - Abd Wahab, Muhammad Amal; Mohd Yusof, Eleena; Ahmad, Rohana; Salleh, Mohd Zaki; Kek, Teh Lay (Malaysian Journal of Medicine and Health Sciences, 2022)
The continuous sequence of bone healing phases starts off with osteoconduction to the implant surface, depending on the migration of osteogenic cells. Osteoneogenesis ensues resulting in a mineralised interfacial matrix and is followed by bone remodelling to the implant interface at discrete sites. Dental implant drilling procedure and placement produce osseous defect which is filled by blood. Within seconds, blood proteins are adsorbed onto the implant surface and platelets are activated resulting in the release of cytokines and growth factors. Further platelet aggregation initiates osteoconduction to the surface, followed by osteoneogenesis, forming an extracellular matrix. Subsequently, remodelling creates a bone to implant interface which can be explained through distance and contact osteogenesis. The dental implant surface has been shown to influence osteoconduction by modifying protein properties and adsorption around the implant. Salivary biomarkers may be considered as a specific and sensitive diagnostic tool to detect these changes in protein expressions after implant placement. Thus, the purpose of this narrative review is to provide a detailed account of the bone healing mechanism associated with dental implant placement, as well as how the implant surface architecture and protein release play a role in bone healing, and the potential use of saliva to detect these biomarkers.